2017
DOI: 10.3892/or.2017.6009
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces ROS via NOX5 in healthy and neoplastic mammary epithelial cells

Abstract: NADPH oxidase (NOX) complexes (a family of seven isoforms) drive cellular ROS production in patho-logical processes such as cancer. NOX-driven ROS production is involved in cell mechanisms from signalling to oxidative stress. Leptin, an adipokine overexpressed in obese patients, has been investigated in studies on breast carcinogenesis, but its effects on oxidative stress remain largely unexplored, especially in breast cancer. The study used three human mammary epithelial cell models presenting different neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…In breast cancer, leptin has been proposed to have a role at different levels (45, 46). At a carcinogenic level, it has been suggested to act as a direct potential activator of short term ROS production in human epithelial mammary cells (47), although other studies previously showed that chronic leptin treatment decreases ROS levels and oxidative stress in MCF-7 cells (48). According to the trophic function of leptin, demonstrated also in MCF7 cells (49), it seems to regulate metabolic reprogramming to promote cellular growth (50).…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
“…In breast cancer, leptin has been proposed to have a role at different levels (45, 46). At a carcinogenic level, it has been suggested to act as a direct potential activator of short term ROS production in human epithelial mammary cells (47), although other studies previously showed that chronic leptin treatment decreases ROS levels and oxidative stress in MCF-7 cells (48). According to the trophic function of leptin, demonstrated also in MCF7 cells (49), it seems to regulate metabolic reprogramming to promote cellular growth (50).…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
“…67 It also activates ROS production in human epithelial mammary cells. 90 Leptin also regulates metabolic reprogramming which promotes cellular growth. 91 All these will modify the microenvironment at adipose tissue that will promote breast cancer development.…”
Section: The Link Between Leptin and Breast Cancermentioning
confidence: 99%
“…NOX5 has also been demonstrated in many non‐immune cells and tissues, including placenta, bone marrow, uterus, stomach, skeletal muscle, cancer cells and hepatocytes and in cells of the cardiovascular system, such as cardiomyocytes, endothelial and vascular smooth muscle cells (Mahbouli et al., ; Montezano et al., ; Yeung et al., ). The functional significance of this widespread expression profile suggests that NOX5 is likely to be important in many (patho)physiological processes in multiple systems that involve ROS.…”
Section: Expression Of Nox5 In Physiological and Pathological Conditionsmentioning
confidence: 99%